2010
DOI: 10.1074/jbc.m109.081356
|View full text |Cite
|
Sign up to set email alerts
|

The l-Cysteine/l-Cystine Shuttle System Provides Reducing Equivalents to the Periplasm in Escherichia coli

Abstract: Intracellular thiols like L-cysteine and glutathione play a critical role in the regulation of cellular processes. Escherichia coli has multiple L-cysteine transporters, which export L-cysteine from the cytoplasm into the periplasm. However, the role of L-cysteine in the periplasm remains unknown. Here we show that an L-cysteine transporter, YdeD, is required for the tolerance of E. coli cells to hydrogen peroxide. We also present evidence that L-cystine, a product from the oxidation of L-cysteine by hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 34 publications
4
94
0
1
Order By: Relevance
“…Because cysteine changed the cellular redox state, leading to greatly increased glutathione disulfide, it was possible that this change also increased the yield of products. Cysteine recently was shown to oxidize the E. coli cytoplasm (28). Using metabolomics and redox-sensitive GFP, we confirmed that cysteine greatly oxidizes E. coli ( Fig.…”
Section: Resultssupporting
confidence: 53%
“…Because cysteine changed the cellular redox state, leading to greatly increased glutathione disulfide, it was possible that this change also increased the yield of products. Cysteine recently was shown to oxidize the E. coli cytoplasm (28). Using metabolomics and redox-sensitive GFP, we confirmed that cysteine greatly oxidizes E. coli ( Fig.…”
Section: Resultssupporting
confidence: 53%
“…EamA and EamB, the representative cysteine exporters of E. coli (13,14), may serve primarily as components of the cysteine/ cystine shuttle system that protects cells from ROS. Moreover, these exporters are highly induced by hydrogen peroxide compared with cysteine, suggesting that their physiological function is to protect cells against ROS (18). CydDC transports cysteine and glutathione (15,17) and mediates cytochrome assembly (47).…”
Section: Discussionmentioning
confidence: 99%
“…However, the specificity of these transporters for cysteine and their significance in controlling cysteine levels as a safety valve are unclear. For example, CydDC and Bcr are primarily transporters of glutathione and multiple drugs (e.g., bicyclomycin), respectively (16,17), and EamA and EamB may function primarily as protection against reactive oxygen species (ROS) (18). Here, we describe two novel systems of Pantoea ananatis, a member of the family Enterobacteriaceae (19), which are directly involved in resistance to excess levels of cysteine through mecha-nisms that mediate cysteine degradation and efflux.…”
mentioning
confidence: 99%
“…SiR activity was estimated by the coupled SiR/OAS-TL assay (Bosma et al, 1991;Khan et al, 2010) with the addition of NADPH and tungstic acid (Brychkova et al, 2012c). The resultant generated Cys was detected as described before (Gaitonde, 1967;Burandt et al, 2001;Ohtsu et al, 2010;Brychkova et al, 2012c). SiR in gel activity detection is based on the detection of sulfide, the direct product of SiR activity, reacting with lead acetate to yield lead sulfide bands (Brychkova et al, 2012c).…”
Section: Protein Extraction and Kinetic Assays For So Apr And Sir Amentioning
confidence: 99%